DEVELOPMENT OF STUDENTS’ COMMUNICATIVE SKILLS IN RUSSIAN LANGUAGE LESSONS - Tojiddinova Mokhlaroy (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. The article analyzes the development of students’ communicative competence in Russian language lessons as one of the main tasks of teaching this subject. Each Russian language lesson, no matter what topic is discussed, should be subordinated to these tasks, taking into account the specifics of the class, the nature of the educational material, and the age characteristics of students.